Parent Perspectives: Part 1-Considerations for Changing the NICU Culture - Jessica N. DiBari; LaToshia Rouse (MDPI AG, 2023)
While publications that aim to reflect the parent perspective are increasingly common in the medical literature, few are authored by parents in their own words. As mothers with lived and professional experience in the Neonatal Intensive Care Unit (NICU), we believe this perspective is vital to improving health outcomes. We are writing from a life course health development framework that regards health as an active process that develops over time with the integration of physical, social, emotional, and relational components. Health development trajectories are shaped by the family and community ecosystems that surround each child. This means that the child's ability to thrive is strongly linked to the family's health and well-being. These links are not being given sufficient attention in clinical practice. Psychological distress, trauma, and grief are common family experiences in the NICU. Left unaddressed, they can negatively impact parent-child bonding. Drawing on life course principles, we make a series of recommendations for changes to practice to enable NICUs to better serve children and families, and better prepare families for the post-NICU experience. These include setting a positive tone in the NICU, creating a nurturing, personalized environment; addressing the social determinants of health; supporting families to develop a 'growth' mindset; and communicating in an optimistic, positive manner. Building trust is key to ensuring families feel supported and can be promoted through establishing equitable collaborative models of care. Peer support, doulas, and community health worker engagement can facilitate early interactions crucial to the child's developmental progress and family healing.